Community Involvement in the Development of Tourism Villages in Turgak Village Belalau Subdistrict West Lampung - Asmaria, Asmaria; Setiawati, Rini; Aziz Apriadi, Eko; Istiqomah, Saniyati (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
The lack of community participation in tourism development in Turgak Village is a significant concern. This study aims to explore public participation in the development of Turgak Village, focusing on transforming it into a tourist destination. The research employs a qualitative design, using interviews and observations, with data analysis conducted through interactive techniques. The findings reveal that public participation in the development of Turgak Village remains low. Contributing factors include limited understanding of the village's tourism potential, reluctance from some residents to engage, and a lack of innovation in tourism development. Despite existing efforts through community initiatives and mutual cooperation, further involvement from local government is necessary to boost participation and improve management. Therefore, recognizing public participation as a key factor in the success of Tourism Village development is crucial.